Chief culture officer how to create a living, breathing corporation - McCracken, Grant David 1951- (New York, NY Basic Books, 2009)
Grant McCracken, an anthropologist who now trains some of the world's biggest companies and consulting firms, argues that the American corporation needs a new professional--a Chief Culture Officer--who would keep a finger on the pulse of contemporary cultural trends while developing a systematic understanding of the deep waves of culture in America and the world.
Includes bibliographical references (p. 215-247) and index.
E-3238G donated by Mr. Johnson Apacible.
Keywords: Management -- Social aspects; Popular culture -- Economic aspects; New products -- Social aspects; Organizational change